Affecting Art and Theory: The Politics of Shame and Creative Academic Performance - Cameron, Jessica Joy (Atlantis, 2016)
In this paper, the author explores their experience of integrating art-making into the academic conference presentation. This practice moves beyond the limitations of the traditional presentation by developing a dialogue between content and form. It is also productive in transgressing the norms of white, middle-class academic decorum and transforming shame into pride.